National security and counterintelligence in the era of cyber espionage - Silva, Eugenie de (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series, 2016)
This book highlights technological advancements in intelligence systems and law enforcement in relation to cybercrime and reconnaissance issues, focusing on current and emergent threats to national security, as well as the technological advancements being adopted within the intelligence field.